The impact of land tenure on deforestation and reforestation in Quilombola territories from 1985 to 2020 in Brazil - Rayna Benzeev; Cauê Bráz; Colleen Scanlan Lyons; Peter Newton (World Development Sustainability)
Land tenure for Indigenous peoples and local communities in forested areas can improve livelihoods and protect forests while recognizing territorial and human rights. Yet little is known about the relationship between land tenure and deforestation within Quilombola territories (QTs) of Afro-descendant populations in Brazil. Understanding these relationships is important given that only 176 of the more than 5,900 QTs have been recognized with legal land tenure rights throughout Brazil. In this study, we conducted a difference-in-differences analysis to estimate the average treatment effect of land tenure on rates of deforestation, reforestation, and net forest cover change from 1985 to 2020 in 313 QTs across all of Brazil as well as 104 more specifically in the Brazilian Amazon and 81 in the Atlantic Forest biome. We additionally tested changes in forest outcomes before and after an earlier stage of the tenure process (incomplete tenure). We found no evidence that formalized land tenure had influenced forest outcomes in QTs. As the first rigorous analysis of the effect of formalized tenure specifically in QTs, our study also reveals several primary knowledge and data gaps relating to Quilombolas. We emphasize the need for much more data to be systematically collected and disseminated on QTs, as well as the need for more research to be conducted to fully understand how tenure influences forest cover in QTs. We highlight that there are considerable opportunities to improve the state of research and understanding about rights, tenure, and forest conservation among Quilombolas, as an important but largely-overlooked (in terms of research) category of traditional peoples in Brazil. We additionally contribute to a growing body of literature on the role of rights-based approaches to conservation.